A 3,500 14C yr. high-resolution record of lake level changes in Lake Titicaca, South America - Abbott, M. B.; Binford, M. W.; Brenner, M.; Kelts, K. R. (Quaternary Research, 1997)
Sediment cores collected from the southern basin of Lake Titicaca (Bolivia/Peru) on a transect from 4.6 m above overflow level to 15.1 m below overflow level are used to identify a new century-scale chronology of Holocene lake-level variations. The results indicate that lithologic and geochemical analyses on a transect of cores can be used to identify and date century-scale lake-level changes. Detailed sedimentary analyses of subfacies and radiocarbon dating were conducted on four representative cores. A chronology based on 60 accelerator mass spectrometer radiocarbon measurements constrains the timing of water-level fluctuations. Two methods were used to estimate the14C reservoir age. Both indicate that it has remained nearly constant at ∼25014C yr during the late Holocene. Core studies based on lithology and geochemistry establish the timing and magnitude of five periods of low lake level, implying negative moisture balance for the northern Andean altiplano over the last 3500 cal yr. Between 3500 and 3350 cal yr B.P., a transition from massive, inorganic-clay facies to laminated organic-matter-rich silts in each of the four cores signals a water-level rise after a prolonged mid-Holocene dry phase. Evidence of other significant low lake levels occurs 2900–2800, 2400–2200, 2000–1700, and 900–500 cal yr B.P. Several of the low lake levels coincided with cultural changes in the region, including the collapse of the Tiwanaku civilization.
id: 173; jpc